A study of bio and tribo modifier on degradation of magnesium-calcium carbonate biomaterial. (2020) - Rajkumar, K.; Ramraji, K.; Namratha, G.; Manoj, S.; Gnanavelbabu, A.
Abstract: Magnesium is emerging as a promising material in biomedical research, especially in the field of orthopedics. However, its potential to be used as an implant is little explored due to its rapid degradation. The stupendous advantage of its innate similarity in properties to that of bones is yet to be exploited. This paper aims at presenting the degradation and tribological properties of Mg-AZ91D calcium carbonate composite with WS2 and hBN as a tribo modifier. A plot of mass loss due to immersion of the composite in simulated body fluid held at 37℃ in addition to wear and coefficient of friction of the composite was discussed. Due to poor interfacial strength, the Mg composite experiences rapid mass loss initially followed by stabilization. Tribo analysis reveals a high wear resistance of the composite than the Mg alloy. The improved wear characteristics of developed biocomposite materials are widely expected to usage in an orthopedic bio implant.